ELECTRONIC-STRUCTURE OF A SINGLE LAYER OF NA ON CU(111) - Fauster, Thomas; et al. (Physical Review B, 1991)
High-resolution photoemission and two-photon photoemission have been used to investigate the electronic structure of a single layer of Na on Cu(111). In addition to an occupied Na-induced state 0.11 +/- 0.03 eV below the Fermi energy, we resolved three unoccupied states with binding energies relative to the vacuum energy of 0.72 +/- 0.03, 0.27 +/- 0.03, and 0.13 +/- 0.04 eV. These values are at variance to the predictions of a simple phase-analysis model. The effective mass of the lowest unoccupied state and the occupied Na-induced state were measured to be m*/m(e) = 1.3 +/- 0.1. This is considerably larger than the expected free-electron value. More refined theoretical models accounting for the atomic structure of the adsorbate are necessary for a realistic description of the electronic structure of single alkali-metal layers on metal surfaces.